Consumer Decision Factors in Purchasing Facial Care Cosmetics - Nindya Dwiana Putri (Jurnal Tata Rias, 2019)
The beauty industry, particularly cosmetics, is growing rapidly. This is accompanied by increasing consumer considerations when choosing a product to purchase cosmetics. The purpose of this study is to identify and analyze the factors influencing consumers' decisions to purchase facial care cosmetics. Nowadays, facial care has become a routine activity for women and men from various backgrounds. In addition to beauty salons, facial treatments are often performed personally due to the ease of obtaining and the wide variety of facial care cosmetics available publicly. The research method used was qualitative, incorporating a literature review. The results of this study indicate that four factors significantly influence consumer decisions to purchase facial care cosmetics: cultural, social, personal, and psychological factors.